Peran Kepuasan Kerja Memediasi Pengaruh Lingkungan Kerja dan Gaya Kepemimpinan terhadap Kinerja Karyawan Gen Z di Denpasar - Ida Ayu Oka Martini; Anak Agung Ngurah Wahyu Baskara (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Employee performance is a key determinant of organizational sustainability, particularly as Generation Z increasingly dominates the workforce with distinct expectations regarding work conditions and leadership. However, misalignment between organizational practices and these expectations often leads to low job satisfaction and suboptimal performance. This study aims to examine the mediating role of job satisfaction in the relationship between work environment, leadership style, and the performance of Generation Z employees in Denpasar City. A quantitative approach was employed using primary data collected from 200 Generation Z employees selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that both the work environment and leadership style have a positive and significant effect on employee performance and job satisfaction. Job satisfaction also exerts a significant positive influence on employee performance. Furthermore, job satisfaction partially mediates the effect of the work environment and leadership style on performance, indicating that supportive organizational conditions enhance performance both directly and indirectly through increased satisfaction. These results contribute to the theoretical understanding of Herzberg’s Two-Factor Theory in the context of Generation Z and provide practical insights for organizations in designing adaptive human resource strategies to improve employee performance and retention.